'I was in control of it from the start': A qualitative study of men's experiences of positive adjustment following a heart attack. (September 2017) - Smith, Fran; Banwell, Elizabeth; Rakhit, Roby
A qualitative design was used to explore the experience of positive adjustment following a heart attack. Ten men attending a cardiac rehabilitation programme completed in-depth semi-structured interviews. An overarching theme: 'I was in control of it from the start' emerged with six subthemes, relating to intrapersonal and interpersonal factors and processes. The subthemes reflected the importance of identifying controllable versus non-controllable factors and employing adaptive coping strategies.